Glycemia, Hypoglycemia, and Costs of Simultaneous Islet-Kidney or Islet After Kidney Transplantation Versus Intensive Insulin Therapy and Waiting List for Islet Transplantation. Issue 10 (October 2015) - Gerber, Philipp A.; Locher, Rebecca; Zuellig, Richard A.; Tschopp, Oliver; Ajdler-Schaeffler, Evelyne; Kron, Philipp; Oberkofler, Christian; Brändle, Michael; Spinas, Giatgen A.; Lehmann, Roger
Abstract : Background: Long-term data of patients with type 1 diabetes mellitus (T1D) after simultaneous islet-kidney (SIK) or islet-after-kidney transplantation (IAK) are rare and have never been compared to intensified insulin therapy (IIT). Methods: Twenty-two patients with T1D and end-stage renal failure undergoing islet transplantation were compared to 70 patients matched for age and diabetes duration treated with IIT and to 13 patients with kidney transplantation alone or simultaneous pancreas-kidney after loss of pancreas function (waiting list for IAK [WLI]). Glycemic control, severe hypoglycemia, insulin requirement, and direct medical costs were analyzed. Results: Glycated hemoglobin decreased significantly from 8.2 ± 1.5 to 6.7 ± 0.9% at the end of follow-up (mean 7.2 ± 2.5 years) in the SIK/IAK and remained constant in IIT (7.8 ± 1.0% and 7.6 ± 1.0) and WLI (7.8 ± 0.8 and 7.9 ± 1.0%). Daily insulin requirement decreased from 0.53 ± 0.15 to 0.29 ± 0.26 U/kg and remained constant in IIT (0.59 ± 0.19 and 0.58 ± 0.23 U/kg) and in WLI (0.76 ± 0.28 and 0.73 ± 0.11 U/kg). Severe hypoglycemia dropped in SIK/IAK from 4.5 ± 9.7 to 0.3 ± 0.7/patient-year and remained constant in IIT (0.1 ± 0.7 and 0.2 ± 0.8/patient-year). Detailed cost analysis revealed US $57, 525 of additional cost for islet transplantation 5 years after transplantation. Based on a 5- and 10-year analysis, cost neutrality is assumed to be achieved 15 years after transplantation. Conclusions: This long-term cohort with more than 7 years of follow-up shows that glycemic control in patients with T1D after SIK/IAK transplantation improved, and the rate of severe hypoglycemia decreased significantly as compared to control groups. Cost analysis revealed that islet transplantation is estimated to be cost neutral at 15 years after transplantation. Abstract : After an average 7-year follow-up, glycemic control and insulin requirements are significantly better in 22 patients with end stage renal failure and islet transplantation when compared to controls. Islet transplantation is estimated to be cost neutral after a 15-year follow-up.